Rapid Induction of Cerebral Organoids From Human Induced Pluripotent Stem Cells Using a Chemically Defined Hydrogel and Defined Cell Culture Medium. (13th May 2016) - Lindborg, Beth A.; Brekke, John H.; Vegoe, Amanda L.; Ulrich, Connor B.; Haider, Kerri T.; Subramaniam, Sandhya; Venhuizen, Scott L.; Eide, Cindy R.; Orchard, Paul J.; Chen, Weili; Wang, Qi; Pelaez, Francisco; et al.
Abstract : This work describes a robust, simple method for generating cerebral organoids from human induced pluripotent stem cells by using a chemically defined hydrogel material and chemically defined culture medium. This method greatly facilitates access to cerebral organoid technology, enables scalable applications, and provides a potential pathway to translational applications where defined components are desirable. Abstract: : Tissue organoids are a promising technology that may accelerate development of the societal and NIH mandate for precision medicine. Here we describe a robust and simple method for generating cerebral organoids (cOrgs) from human pluripotent stem cells by using a chemically defined hydrogel material and chemically defined culture medium. By using no additional neural induction components, cOrgs appeared on the hydrogel surface within 10–14 days, and under static culture conditions, they attained sizes up to 3 mm in greatest dimension by day 28. Histologically, the organoids showed neural rosette and neural tube-like structures and evidence of early corticogenesis. Immunostaining and quantitative reverse-transcription polymerase chain reaction demonstrated protein and gene expression representative of forebrain, midbrain, and hindbrain development. Physiologic studies showed responses to glutamate and depolarization in many cells, consistent with neural behavior. The method of cerebral organoid generation described here facilitates access to this technology, enables scalable applications, and provides a potential pathway to translational applications where defined components are desirable. Significance: Tissue organoids are a promising technology with many potential applications, such as pharmaceutical screens and development of in vitro disease models, particularly for human polygenic conditions where animal models are insufficient. This work describes a robust and simple method for generating cerebral organoids from human induced pluripotent stem cells by using a chemically defined hydrogel material and chemically defined culture medium. This method, by virtue of its simplicity and use of defined materials, greatly facilitates access to cerebral organoid technology, enables scalable applications, and provides a potential pathway to translational applications where defined components are desirable.